The evaluation of Phenrica sp.2 (Coleoptera: Chrysomelidae: Alticinae), as a possible biological control agent for Madeira vine, Anredera cordifolia (Ten.) Steenis in South Africa - Van der Westhuizen, Liamé (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2006)
Anredera cordifolia (Basellaceae), Madeira vine, is a perennial, semi- succulent climber native from Paraguay to southern Brazil and northern Argentina. It has a history of weediness and difficulty of control once established. In South Africa Madeira vine has a wide range and distribution with altitudes ranging from 10-1800m above sea level. Described as a transformer species, its sheer weight is capable of breaking branches off trees, causing the potential collapse of forest canopies. Chemical and mechanical control methods are expensive, labour intensive and may provide only temporary relief. A biological control programme was therefore initiated in 2003. Cf Phenrica sp. 2 (Coleoptera: Chrysomelidae: Alticinae), was field collected from A. cordifolia in Brazil, SSW of Cascavel in the Paraná Province during a survey in November 2003. Eggs are laid in groups of 16 with the average fertility rate being 89%. After going though three larval instars, the larvae pupate in the soil with the adults eclosing after a period of 17 days. The total developmental time for a generation from egg to egg ranges between 7-8 weeks. Biological traits that favour the flea beetle as a possible biological control agent include long-lived adults (up to 5 months) and multiple generations during the summer period. Both adults and larvae feed extensively on leaves and stems and although developmental rates will slow down during the winter period, no indication of a definite diapause was found under the prevailing laboratory conditions. After completing the larval no-choice trials with twenty-six plant species from 14 plant families Phenrica sp. 2 proved to be adequately host specific, as larval development was only supported by 3 Basellaceae species (including the control A. cordifolia) and one Portulacaceae species. All of these are introduced species in South Africa. The only indigenous Basella species could not be tested as it has a very marginal distribution, and because it's inconspicuous nature, it is seldom seen or collected. Adult multi-choice trials were restricted to species that could sustain larval development to give some indication of the acceptability of these species for adult feeding and oviposition. Although adult feeding was initially concentrated on B. alba, the oviposition preference was clear-cut as females only oviposited on A. cordifolia. In order to quantify the impact of Phenrica sp. 2 on plant biomass and to assess the incidence and intensity of foliar damage, a pair of adults was confined to the host plant, for 2 generations, with different levels of larval densities. The results indicated that the host plant, due to both larval and adult feeding, suffered leaf losses of up to 55%. Anredera cordifolia was however still capable of enlarging the root mass despite suffering huge leaf losses. This would imply that A. cordifolia has an effective re-growth capacity and it will only be vulnerable to attack of the storage organs that enable re-growth, or to repeated attack of other plant parts through which reserves are exhausted. Unfortunately the period of exposure (24 days) was too short to prove that Phenrica sp. 2 impacts on the below ground dry mass, but should the plant be completely defoliated, as was observed in the field, the host plant would be forced to deplete stored resources. Phenrica sp.2 has shown to be very host specific and although A.cordifoia loses its leaves during the winter period in most provinces in South Africa, the adults are long-lived and should be able to survive the leafless periods. Further more the relatively short life cycle, high fecundity and 3 generations per year should theoretically insure a strong population build-up that would improve the chances of establishment in the field. All indications are that Phenrica sp. 2 is an agent well worth considering for the biological control of A. cordifolia.
Keywords: Weeds -- Biological control -- South Africa; Biological pest control agents -- South Africa; Invasive plants -- Biological control -- South Africa; Chrysomelidae; Beetles; Flea beetles; Anredera cordifolia -- Biological control